(3GdaUhd GdEjdGbjI aj cdjGJ GdWHs - (3TQa GdOjf CHj YHO Gddg eMeO Hf jhSa GdEjdGbjs
(3ChdgG (B:s
(3GdMeO ddg GdZfi GdMejO Cbhd (B: (3Ef GdWH jYQa efg CMhGd HOf GdEfSGf ef LgI eG jUM , hjRhd Yf GdUMI , dJMaX GdUMI MGUdI , hJSJQO RGFdI s
(3BNQgG (B:s
(3ENJdWJ ChQGbg eY TQM GdCSHGH hGdYdGeGJ hef Ke LGAJ gPg GdYHGQI Je MeO Gddg bQG HGPjf CSHGH hYdGeGJ GdSeQbfOi s
(3Vef eLehY , JQJjHgG (B: (3ef U H (B86 - (3U C (B260s
(3fSNI KGfjI fajSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B170 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGj (B(6406) s
Keywords: (3GdWHs